Species Specificity of Protein Kinase R Antagonism by Cytomegalovirus TRS1 Genes - Child, Stephanie J. (American Society for Microbiology, 2012)
The host antiviral protein kinase R (PKR) has rapidly evolved during primate evolution, likely in response to challenges posed by many different viral antagonists, such as the TRS1 gene of cytomegaloviruses (CMVs). In turn, viral antagonists have adapted to changes in PKR. As a result of this “arms race,” modern TRS1 alleles in CMVs may function differently in cells derived from alternative species. We have previously shown that human CMV TRS1 (HuTRS1) blocks the PKR pathway and rescues replication of a vaccinia virus mutant lacking its major PKR antagonist in human cells. We now demonstrate that HuTRS1 does not have these activities in Old World monkey cells. Conversely, the rhesus cytomegalovirus homologue of HuTRS1 (RhTRS1) fulfills these functions in African green monkey cells, but not rhesus or human cells. Both TRS1 proteins bind to double-stranded RNA and, in the cell types in which they can rescue VVΔE3L replication, they also bind to PKR and prevent phosphorylation of the α-subunit of eukaryotic initiation factor 2. However, while HuTRS1 binds to inactive human PKR and prevents its autophosphorylation, RhTRS1 binds to phosphorylated African green monkey PKR. These studies reveal that evolutionary adaptations in this critical host defense protein have altered its binding interface in a way that has resulted in a qualitatively altered mechanism of PKR antagonism by viral TRS1 alleles from different CMVs. These results suggest that PKR antagonism is likely one of the factors that contributes to species specificity of cytomegalovirus replication.